Genotoxic and hematological effects of endocrine disruptive chemicals, bisphenol a and nonylphenol, on Nile tilapia (Oreochromis niloticus) / Muhammad Faris Sahardin - Muhammad Faris , Sahardin (2020)
This study was performed to evaluate the genotoxicity and hematology effects of single and binary exposure of bisphenol A and nonylphenol towards Oreochromis niloticus. O. niloticus was singly exposed to bisphenol A at concentration of 2 mg/l and nonylphenol at concentration of 0.04 mg/l in 16 L glass tank. O. niloticus was also synergistically exposed to the both concentration of 2 mg/l of bisphenol A and 0.04 mg/l of nonylphenol. Four fishes were randomly used for four exposures after two weeks acclimatization. All of them were exposed to the compound for 96 hours without water change prior observation. Fishes were anaesthetized and sacrificed for blood for the analysis of micronucleus, comet assay and hematology. The observation showed significant difference in the micronuclei frequency and nuclear abnormalities frequency in micronucleus test when they were singly exposed to 0.04 mg/l of nonylphenol. The obvious strand breakage of supercoiled duplex DNA had been determined in the comet assay analysis in single exposure of 0.04 mg/l of nonylphenol compared to others. Result from complete blood count also showed nonylphenol exposure at concentration 0.04 mg/l caused significant difference in some blood parameters when compared to the control. Based on this study, it was proved that single exposure of nonylphenol contributed stronger effect to O. niloticus compared to single exposure of bisphenol A and binary exposure of both chemicals.